Factors affecting exercise intensity in professional rugby league match-play - Kempton, T.; Coutts, A. J. (Journal of Science and Medicine in Sport, 2016)
Objectives: To examine the effects of match-related and individual player characteristics on running performance in professional rugby league matches. Design: Longitudinal observational study. Methods: Global positioning system (GPS) and technical performance measures (attacking involvements and tackles made) were collected from 23 players competing in the National Rugby League (NRL) over 24 matches during a season. The GPS data were categorised into relative total distance (m min-1) and relative high-speed running distance (HSR m min-1, >14.4 km h-1). Each match was classified according to season phase, location, recovery length, opposition strength and result. Individual player fitness status was obtained from a 1.2-km shuttle run test conducted prior to the start of the season. Two separate linear mixed models were constructed to examine the influence of match-related and individual player characteristics on relative total and HSR distances. Results: Matches played away from home, early in the season and following short recovery cycles were associated with reduced relative total and HSR distances. Matches won contained less relative total and HSR distance; whereas only HSR distance was higher against weaker opposition. The total time the ball was out of play reduced relative total but not HSR distances. The number of defensive but not attacking involvements influenced both physical performance measures. Finally, player fitness was positively related to both relative total and HSR distances. Conclusions: There appears to be a complex interplay of factors affecting match-running performance in rugby league. The results underline the importance of considering contextual factors when analysing rugby league match-activity profiles.